An experimental study of corporate social responsibility through charitable giving in Bertrand markets - Feicht, Robert; Grimm, Veronika; Seebauer, Michael (Journal of Economic Behavior & Organization, 2016)
We experimentally investigate a Bertrand market with homogenous goods in which sellers can announce the donation of a share of their profits to an existing non-profit organization. In a 2 × 2 design, we vary the credibility of announcements and the efficiency of the contributions to the public fund. We find that sellers’ donations are strictly positive independently of the credibility of the announcements, and their donations are higher if announcements are credible and efficiency is high. However, market outcomes in terms of prices and profits do not differ significantly in any treatment that allows for contributions to a public fund. Analysis of buyer decisions reveals that prices are the main driver of purchase decisions while higher donations only affect purchase decisions when they are credible and price differences are negligible. Our results indicate that under intense competition the possibility of attracting customers through corporate social responsibility activities is limited, although the constant positive level of contributions suggests that norms lead to a certain minimum level of corporate social responsibilit
Keywords: Corporate social responsibility; Competition; Charitable giving; Experiment

Bargaining over waiting time in gain and loss framed ultimatum games - Doll, Monika; Seebauer, Michael; Tonn, Maren (2017)
We implement waiting time as a currency in an ultimatum game in an experimental laboratory study. Subjects had to split 60 minutes of waiting time. We analyze bargaining behavior in varying situations connected to waiting time as well as gain and loss framing. Different situations that follow waiting time have no influence on bargaining behavior. Regarding gain and loss framing, we do not find dierences in proposers' behavior. Responders show less willingness to wait when the bargaining outcome is framed as a loss compared to being framed as a gain of time. Displaying less willingness to wait, responders show a higher propensity to risk a rejection of the proposers' offer
Keywords: Ultimatum Game; Waiting Time; Experimental Currency; Leaving the Laboratory; Framing

Does Direct Democracy Foster Efficient Policies? An Experimental Investigation of Costly Initiatives - Seebauer, Michael (2015)
This study investigates the effects of the provision of costly initiatives on policy efficiency in a laboratory experiment where a policy setter implements a status quo affecting the utility of the constituency. I vary treatments regarding the political institution (either purely representative or direct democracy where the status quo may be contested by the costly proposal of an alternative) and the appointment of the policy setter (either random or by election). In accordance to theoretical predictions, the experimental data reveal a substantial indirect effect of direct democracy inducing higher efficiency levels by serving as a credible threat towards the policy setter without actually being used. Moreover, the initiative impedes excessive candidate competition during elections reducing campaign costs and thus increasing overall efficiency. In contrast to theoretical predictions, the initiative is actually employed frequently, so there is also a sizeable direct effect of the initiative. However, this effect is generally overcompensated by the costs induced by the proces
Keywords: Direct democracy; Policy decision; Efficiency; Laboratory experiment

Information acquisition and revelation in committees: An experimental study - Großer, Jens; Seebauer, Michael (2019)
We experimentally study compulsory majority voting over two alternatives in small committees. The committee members share a common interest, and each member decides on whether to buy a private signal about which alternative better suits their interest. A signal is valuable but only imperfectly indicates the better alternative. In the experiment, both standing and ad hoc committees perform on average poorly, but the former committees do even worse and have a much higher performance variation than the latter ones. We attribute the low efficiency to limited feedback about the informational efforts of co-members, which impedes coordination and proper evaluation of their intention to cooperat
Keywords: Voting behavior; committees; laboratory experiment

Physician behavior under prospective payment schemes: Evidence from artefactual field and lab experiments - Hafner, Lucas; Reif, Simon; Seebauer, Michael (2017)
Recent experimental studies analyze the behavior of physicians towards patients and find that physicians care for their own profit as well as patient benefit. In this paper, we extend the experimental analysis of the physician decision problem by adding a third party representing the health insurance which finances medical service provision. Our results show that physicians take into account the payoffs of the third party, which can lead to underprovision of medical services. We conduct a laboratory experiment in neutral as well as medical framing using students and medical doctors as subjects. Subjects in the medically framed experiments behave weakly more patient orientated in contrast to neutral framing. A sample of medical doctors exhibits comparable behavior to students with medical framing.<br
Keywords: health economic experiment; framing; physician behavior; prospective payment schemes

Physician behavior under prospective payment schemes—evidence from artefactual field and lab experiments - Reif, Simon; Hafner, Lucas; Seebauer, Michael (International Journal of Environmental Research and Public Health, 2020)
Recent experimental studies analyze the behavior of physicians towards patients and find that physicians care for their own profit as well as patient benefit. In this paper, we extend the experimental analysis of the physician decision problem by adding a third party which represents the health insurance that finances medical service provision under a prospective payment scheme. Our results show that physicians take into account the payoffs of the third party, which can lead to underprovision of medical care. We conduct a laboratory experiment in neutral as well as in medical framing using students and medical doctors as subjects. Subjects in the medically framed experiments behave weakly and are more patient orientated in contrast to neutral framing. A sample of medical doctors exhibits comparable behavior to students with medical framing.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Framing; Health economic experiment; Physician behavior; Prospective payment schemes

Reputation formation in economic transactions - Abraham, Martin; Grimm, Veronika; Neeß, Christina; Seebauer, Michael (Journal of Economic Behavior & Organization, 2016)
We investigate patterns of information transmission and the evolution of behaviour in standard trust games where reputational information can be exchanged between individual agents within a population, but does not become public. We vary the nature of information that could be transmitted (either a subjective rating or the objective details of a transaction), as well as the cost of information transmission (either zero or positive). We find that information transmission is heavily used if it is costless but only moderately if it has positive cost. Objective information effectively increases the average amount sent in the trust game (and thus, efficiency and average profits) as well as the return rate only if transmission is costless and therefore is heavily used. Subjective information (a rating) only increases transfer and return rates in a control treatment where it becomes publicly available, but not for private communication. A detailed analysis of the determinants of information transmission shows a positive influence of (a) the transfer made to a receiver, (b) experience of exploitation, and (c) points to reciprocity in information transmissio
Keywords: Reputation formation; trust game; reciprocity; experiments

Reputation formation with competitive investors - Abraham, Martin; Grimm, Veronika; Neeß, Christina; Seebauer, Michael (2018)
We investigate patterns of information transmission and its effects on transfer and return rates in a standard investment game where investors compete in a tournament and costless reputational information about responders can be exchanged between individual investors within a population but does not become public. We vary the nature of information that could be transmitted (either a subjective rating or the objective details of a transaction) and compare the level of information exchange to a treatment without competition among investors. We find that competition among investors decreases information transmission substantially and significantly, but the nature of information only affects information transmission decisions without competition. When investors compete they exhibit lower transfer rates and profits, while responders return lower rates and are only able to significantly increase their profits when information is objective. We find evidence that in a competitive environment investors deliberately use subjective information to mislead their competitor

The curse of uninformed voting: An experimental study - Großer, Jens; Seebauer, Michael (Games and Economic Behavior, 2016)
We study majority voting over two alternatives in small groups. Individuals have identical preferences but are uncertain about which alternative can better achieve their common interest. Before voting, each individual can obtain information by buying a valuable but imperfect signal about the better alternative. Voting is either voluntary or compulsory. In the compulsory mode, each individual must vote between the two alternatives, while in the voluntary mode they can also abstain. An uninformed, random vote generates a negative externality since it may override an informative group decision in pivotal events. In our experiments, participants in randomly re-matched groups obtain information more often with compulsory than voluntary voting, and the average number of signals is greater in larger than smaller groups. Surprisingly, uninformed voting is common even in the voluntary mode! Finally, group performance is poor in all treatments, indicating the need to reconsider current practice of jury and committee votin
Keywords: Voting behavior; voluntary and compulsory voting; information search and aggregation; Condorcet Jury model; laboratory experiments

The role of reciprocity in the creation of reputation - Abraham, Martin; Damelang, Andreas; Grimm, Veronika; Neeß, Christina; Seebauer, Michael (European Sociological Review, 2021)
Although reputation has been shown to solve problems of information and opportunism in business relationships, knowledge about the emergence of reputation in business relationships beyond the internet is considerably scarcer. In this paper, we argue that a norm of reciprocity is a major driver for information transfer in social and economic systems. A social norm to return the favors that are given by others will enhance the flow of information about potential exchange partners. We distinguish between direct and generalized reciprocity and argue that both may foster the flow of information about exchange partners in economic systems. Moreover, we examine the interdependency between competition and reciprocity. Our empirical evidence is based on a laboratory experiment with students and a field experiment with 240 managers of a German business cluster. Our results show that direct reciprocity, in particular, is a major driver for the transmission of reputational information to third parties. Moreover, transmission costs and competition reduce the willingness to produce information in an exchange syste